2020
DOI: 10.1001/jamanetworkopen.2020.3612
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-Associated Nephrotoxic Effects in Children

Abstract: Cisplatin has been an important component of chemotherapy for cure and control of several pediatric and adult malignant tumors. Nephrotoxic effects of cisplatin are a limitation of cisplatinbased chemotherapy and are often prohibitive of further treatment with cisplatin, when they occur.However, this adverse effect is not uniformly manifested among all patients who receive cisplatinbased chemotherapy. 1 During the past few decades, investigators have attempted to identify risk factors that predispose certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Of concern, long‐term adverse health effects among children receiving cancer treatments have been described in various studies. For instance, it has been shown that radiation to the pancreas increases the risk of diabetes mellitus 4 or chemotherapy results in gonadotoxicity, 5 ototoxicity, 6 or nephrotoxicity 7 in children. Besides, several investigations have shown that chemotherapeutic agents affect the proliferative capacity of growth plate chondrocytes, leading to a decrease in growth rate 8–11 .…”
Section: Introductionmentioning
confidence: 99%
“…Of concern, long‐term adverse health effects among children receiving cancer treatments have been described in various studies. For instance, it has been shown that radiation to the pancreas increases the risk of diabetes mellitus 4 or chemotherapy results in gonadotoxicity, 5 ototoxicity, 6 or nephrotoxicity 7 in children. Besides, several investigations have shown that chemotherapeutic agents affect the proliferative capacity of growth plate chondrocytes, leading to a decrease in growth rate 8–11 .…”
Section: Introductionmentioning
confidence: 99%
“…Accepted: April 27, 2022 2012). However, its use is associated with serious side effects, including ovarian toxicity (Motwani and Curhan, 2020;Rybak et al, 2019). This toxicity is due to an imbalance between antioxidant capacity and reactive oxygen species (ROS) production, which leads to mitochondrial and DNA damage and consequent follicle death (Barberino et al, 2017;Lins et al, 2020).…”
Section: Introductionmentioning
confidence: 99%